THE DEVELOPMENT OF STUDENT ACTIVITY SHEETS (SAS) BASED ON GUIDED DISCOVERY TO PRACTICE SCIENCE LITERACY IN ACID BASE MATERIALS (Universitas Negeri Surabaya, 2019)
Student Activity Sheet (SAS) based on guided discovery learning model is needed to improve students scientific literacy. The purpose of this study is to analyze the feasibility (validity, practicality, and effectiveness) of SAS based on guided discovery to train scientific literacy in acid-base material. The type of research used in this study is research and development (R & D). The instruments used in this study are the contents and construct validation sheets, student response sheets, student activity observation sheets, and the pretest-posttest sheet. The results showed that: (1) The validity content and construct validity obtained Highly Valid criteria with a percentage range between 83.4% -86.7% in all aspects; (2) Practicality includes the activities and responses of students. In the activity obtained very practical criteria with a percentage range of 91.67% -100%. In the students response, practical and very practical criteria were obtained with a percentage range of 66.7% -100%; (3) Effectiveness includes tests of student learning outcomes and students scientific literacy tests. In the learning outcomes test, all students are declared complete with a value range of 80-100. In the scientific literacy test, getting the N-gain value with a range of 0.8-1 with the gain score criterion is at high criteria. Keywords: Guided Discovery, Science Literacy, Acid Base